(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The Etruscan writings found in Italy and the lexical substratum of unknown origin in Latin and Old Greek languages have long been in the focus of attention of linguists. A significant number of names in Old and Roman onomasticon are discovered to be Old Turkic lexicon. The most important source to reveal the ethnical origin of these people in the Etruscan writings found in the territory of Italy. Turkic character of the Etruscan language is achieved comparatively with Turkic languages. The leading part of the Etruscan lexicon and morphology is found to be Old Turkic.